2020
DOI: 10.1080/01446193.2019.1702251
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting basics: theoretically-grounded interesting research that addresses challenges that matter

Abstract: Revisiting basics: theoretically-grounded interesting research that addresses challenges that matter In this editorial, I reflect on my last 6 years as associate editor for Construction Management and Economics to explain common problems found in manuscripts rejected in our peer-review process. These issues highlight the importance of engaging with current conversations in and related to the field, and the need to strengthen our contributions so that we as a collective community can advance and challenge funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Several studies, including Fellows and Liu (2015), have noted that the positivist/reductionist approach to carrying out construction research, aligns more with the natural and engineering sciences. The engineering ontology/world view possibly explains why Construction Management research has a well-documented history of research primarily focused on identifying factors that impact project performance improvements (Chan, 2020). Panas and Pantouvakis (2010), investigated the various forms of positivist approach mostly deployed in construction productivity studies.…”
Section: The Philosophical Debate In Construction Management Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies, including Fellows and Liu (2015), have noted that the positivist/reductionist approach to carrying out construction research, aligns more with the natural and engineering sciences. The engineering ontology/world view possibly explains why Construction Management research has a well-documented history of research primarily focused on identifying factors that impact project performance improvements (Chan, 2020). Panas and Pantouvakis (2010), investigated the various forms of positivist approach mostly deployed in construction productivity studies.…”
Section: The Philosophical Debate In Construction Management Researchmentioning
confidence: 99%
“…More recently, Chan's (2020) editorial reported that the majority of 350 manuscripts received by 'Construction Management and Economics' were primarily based on 'self-perception and self-reporting questionnaires surveys', and as such rarely made it through to peer-review (p. 2). These figures indicate that construction industry researchers continue to tow the positivist logic, to understand the complexity of socially derived organizational issues.…”
Section: The Philosophical Debate In Construction Management Researchmentioning
confidence: 99%
See 3 more Smart Citations